2022
DOI: 10.1063/5.0071106
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence-driven magnetic reconnection and the magnetic correlation length: Observations from Magnetospheric Multiscale in Earth's magnetosheath

Abstract: Turbulent plasmas generate a multitude of thin current structures that can be sites for magnetic reconnection. The Magnetospheric Multiscale (MMS) mission has recently enabled the detailed examination of such turbulent current structures in Earth's magnetosheath and revealed that a novel type of reconnection, known as electron-only reconnection, can occur. In electron-only reconnection, ions do not have enough space to couple to the newly reconnected magnetic fields, suppressing ion jet formation and resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 148 publications
(132 reference statements)
1
47
0
Order By: Relevance
“…Standard reconnection has also been observed to occur in Earth's turbulent magnetosheath (e.g., Retinò et al., 2007; Stawarz et al., 2022). However, Phan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard reconnection has also been observed to occur in Earth's turbulent magnetosheath (e.g., Retinò et al., 2007; Stawarz et al., 2022). However, Phan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Such electron-scale magnetic reconnection without ion coupling is therefore referred to as electron-only reconnection (e.g., Pyakurel et al, 2019). Further studies have shown that electron-only reconnection occurs pervasively in turbulent plasmas, not only in the magnetosheath (Lu et al, 2021;Stawarz et al, 2019Stawarz et al, , 2022) but also at Earth's bow shock (Gingell et al, 2019(Gingell et al, , 2020.…”
mentioning
confidence: 99%
“…The estimated shock normal angle is therefore θ bn ≈ 36°, corresponding to a Q ‖ shock. In the MSH, B (Figure 1a) has an average magnitude 〈B〉 = 21 nT and fluctuations of 𝐴𝐴 𝐴𝐴𝐴𝐴∕⟨𝐴𝐴⟩ = √ ⟨|(𝑩𝑩(𝑡𝑡) − ⟨𝑩𝑩⟩)| 2 ⟩∕⟨𝐴𝐴⟩ = 0.92 , which falls in the range of statistically observed fluctuation levels in the MSH (Stawarz et al, 2022).…”
Section: Whistler Observationsmentioning
confidence: 81%
“…A recent development in the study of reconnection has been the observation of purely electron‐scale reconnection regions, in which ions do not participate in the reconnection process (Gingell et al., 2019, 2020, 2021; Phan et al., 2018; Stawarz et al., 2022; Wang et al., 2019). This differs from the standard picture of collisionless reconnection (Ishizawa et al., 2004; Malyshkin, 2008; Yamada, 2011), where the reconnection region consists of an electron‐scale layer within a wider ion‐scale diffusion region.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we focus on reconnection in the turbulent environment downstream and in the transition region of quasi‐parallel shocks. Numerous electron‐scale current sheets are observed in these regions, leading to a favorable environment for electron‐scale reconnection (Gingell et al., 2017, 2019, 2020, 2021; Phan et al., 2018; Sharma Pyakurel et al., 2019; Stawarz et al., 2022; Wang et al., 2019). While existing kinetic simulation studies in the shock environment have shown reconnection at both electron and ion scales, the simulations have been two‐dimensional (Bessho et al., 2019; Bessho et al., 2020, 2022; Q. Lu et al., 2021), restricting reconnection to a single plane.…”
Section: Introductionmentioning
confidence: 99%